Recent progress in the development of backplane thin film transistors for information displays - Ji, Dongseob; Jang, Jisu; Park, Joon Hui; Kim, Dasol; Rim, You Seung; Hwang, Do Kyung; Noh, Yong-Young (한국정보디스플레이학회, 2021)
This review aims to provide a technical roadmap and progress update for backplane thin film transistors (TFTs) used in organic light emitting diodes flat panel displays and next-generation flexible displays. In the introduction, we provide a general overview as well as trends in research on backplane TFTs. The main section describes current technical level and future prospects for amorphous metal oxide, semiconducting carbon nanotube, 2D transition metal dichalcogenide, and organic TFTs. The summary and prospects are provided in the conclusion.